2012
DOI: 10.1007/s10071-012-0500-3
|View full text |Cite
|
Sign up to set email alerts
|

Worms under cover: relationships between performance in learning tasks and personality in great tits (Parus major)

Abstract: In animals, individual differences in learning ability are common and are in part explained by genetic differences, developmental conditions and by general experience. Yet, not all variations in learning are well understood. Individual differences in learning may be associated with elementary individual characteristics that are consistent across situations and over time, commonly referred to as personality or temperament. Here, we tested whether or not male great tits (Parus major) from two selection lines for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 32 publications
2
48
3
Order By: Relevance
“…Previously we found no link between EB and PSP in our population, albeit with a smaller sample size [81], though EB has been linked to cognitive traits in some tit populations [86,87].…”
Section: (A) the Study Systemcontrasting
confidence: 76%
“…Previously we found no link between EB and PSP in our population, albeit with a smaller sample size [81], though EB has been linked to cognitive traits in some tit populations [86,87].…”
Section: (A) the Study Systemcontrasting
confidence: 76%
“…Various protocols to assess cognitive abilities have been developed for captive songbirds (e.g. Boogert et al 2011;Amy et al 2012) and have been successfully implemented in studies examining the effects of developmental stress on learning impairments into adulthood (Fisher et al 2006;Kriengwatana et al 2015). It would be prudent to conduct additional cognitive tests for two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fast-explorers learn new appetitive tasks more quickly than slow-explorers (black-capped chickadees Poecile atricapillus Guillette et al, 2009; Panamanian bishop fish Brachyrhaphis episcopi DePasquale et al, 2014), whereas slow-explorers perform better than fast-explorers on reversal learning (black-capped chickadees Guillette et al, 2011;great tits Verbeek et al, 1994; but see Amy et al 2012 where the oppostie was found in great tits) or avoidance learning tasks (great tits ExnerovĂĄ et al, 2010). Most of the experiments on exploratory behavioural and cognition have focused on variation in learning speed (also called learning rate, e.g., trials to reach learning criteria, marked with 'A' for information acquisition in Table 1).…”
Section: Introductionmentioning
confidence: 99%